2018
DOI: 10.29244/j.agromet.32.2.81-92
|View full text |Cite
|
Sign up to set email alerts
|

Development of Early Detection Method for Drought and Flood on Rice Paddy

Abstract: <p>Droughts and floods due to extreme climate events has caused yield loss in various regions of Indonesia, including the Provinces of Aceh and North Sumatra. An early detection model needs to be developed to anticipate the negative impacts of extreme climate event. The model may describe the association of surplus and rainfall deficits with paddy damage due to drought and flood. We used Standardized Precipitation Index (SPI) to explore drought and flood characteristics in period 1989-2016. The study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In Indonesia, El Niño associated with prolong dry season (Hidayati and Chrisendo, 2010;Supari et al, 2018;Wahab et al, 2009), whereas La Niña relate to high rainfall (Hidayat et al, 2018). Prolonged dry season triggered by El Niño has caused severe impacts on agriculture (Mulyaqin, 2020;Nóia Júnior and Sentelhas, 2019;Surmaini et al, 2018), water resource (Taufik, 2010), and environment (Chapman et al, 2020). The most pronounce impacts is land and forest fires that causing severe peat land degradation (Sze and Lee, 2019) and health related issues (Demissie and Mengisitie, 2017) such as in 1997 and 2015 fires.…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, El Niño associated with prolong dry season (Hidayati and Chrisendo, 2010;Supari et al, 2018;Wahab et al, 2009), whereas La Niña relate to high rainfall (Hidayat et al, 2018). Prolonged dry season triggered by El Niño has caused severe impacts on agriculture (Mulyaqin, 2020;Nóia Júnior and Sentelhas, 2019;Surmaini et al, 2018), water resource (Taufik, 2010), and environment (Chapman et al, 2020). The most pronounce impacts is land and forest fires that causing severe peat land degradation (Sze and Lee, 2019) and health related issues (Demissie and Mengisitie, 2017) such as in 1997 and 2015 fires.…”
Section: Introductionmentioning
confidence: 99%
“…The weather variable that most concerned is rainfall because it typically has a high variability and it affects many sectors of human activities. Prolonged rainfall may lead to flood events (Ciric et al, 2017;Suciantini and Hidayat, 2006;Surmaini et al, 2018), while the absent of rainfall for a long period will trigger drought associated wildfire in humid tropics (Taufik, 2010;Taufik et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Climate related studies in Indonesia showed that extreme weather events are closely related to various natural disasters, such as drought (King et al, 2016;Surmaini et al, 2018;Taufik et al, 2020Taufik et al, , 2017, floods (Lestari and Dasanto, 2019;Narulita and Ningrum, 2018), and frost (Pradana et al, 2018a(Pradana et al, , 2018b. The disasters influence many sectors in Indonesia specially the agricultural sector (Amalo et al, 2017;Kim et al, 2019;Kuswanto et al, 2019;Lesk et al, 2016;Mulyaqin, 2020), which indirectly affect national economic conditions (Boer and Surmaini, 2020;Chatzopoulos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Most researches in Indonesia discuss how climate variability impacts on agriculture in lowland area (e.g. Mulyaqin, 2020;Surmaini et al, 2018), but limited studies explained how agriculture in highland are influenced by extreme weather events such as frost (Pradana et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%